1997
DOI: 10.1148/radiographics.17.4.9225397
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric case of the day. Mesenteric plexiform neurofibroma in neurofibromatosis type 1 (von Recklinghausen disease).

Abstract: Radiograph of the abdomen obtained with the patient prone during a small bowel followthrough study demonstrates marked separation of bowel loops. The bowel wall is diffusely thickened, and mass effect is seen on the barium-filled loops of bowel. The cecum (arrowheads) is displaced medial to adjacent loops of small bowel. Calcifications are not present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Typical CT findings of plexiform neurofibromatosis are homogeneously low-attenuated masses extending from the mesenteric root to the involved bowel wall. Similarly to mesenteric lymphangioma, signal intensity is increased on T2-weighted MR images [8]. However, Fukuya et al reported that CT of mesenteric neurofibromatosis shows characteristic clusters of small, mass-like areas of softtissue attenuation that are caused by the trapping of normal fat among the entangled peripheral nerve network [9] and differ from images of mesenteric lymphangioma.…”
Section: Discussionmentioning
confidence: 99%
“…Typical CT findings of plexiform neurofibromatosis are homogeneously low-attenuated masses extending from the mesenteric root to the involved bowel wall. Similarly to mesenteric lymphangioma, signal intensity is increased on T2-weighted MR images [8]. However, Fukuya et al reported that CT of mesenteric neurofibromatosis shows characteristic clusters of small, mass-like areas of softtissue attenuation that are caused by the trapping of normal fat among the entangled peripheral nerve network [9] and differ from images of mesenteric lymphangioma.…”
Section: Discussionmentioning
confidence: 99%